(untitled) (Physical Education, Health and Social Sciences, 2025)
Introduction: Major depressive disorders (MDD) are increasing in our society and there is a high risk of suicidal attempt in patients with depression. Objective: To determine the frequency of suicidal attempt in patients presenting with major depressive disorders. Patients AND METHODS: This Cross-sectional study was conducted at the department of Psychiatry Bolan Medical Complex hospital Quetta from 13-06-2014 to 15-06-2015. Patients fulfilling the inclusion criteria Taking a thorough history from all the patients and doing mental state examination, the final diagnosis is made according to ICD-10 criteria for depressive disorder. Diagnosis of depression with suicide attempt was made by two consultant psychiatrists. The severity of depressive disorder was assessed by applying HAM-D rating scale for depression version 17. Its scores can be interpreted as minimal or no depression (0-7), Mild (8- 17), Moderate (18-25), Sever (26+). Were enrolled for study. After taking history and performing mental state examination, the final diagnosis is made according to ICD-10 criteria for depressive disorder. Diagnosis of depression with suicide attempt was made by two consultant psychiatrists. The severity of depressive disorder was assessed by applying HAM-D rating scale for depression version 17. Results: 0ut of 130 patients, 72(55.38%) majority of female and 58(44.62%) male with mean age of 28.52 ± 7.80 years and mean duration of disease 3.31 ± 1.467 years were included with minimum and maximum duration its between 1year to 6 years. Eighty-one (62.31%) patients belong to lower class, 44(33.85%) middle and 5(3.85%) were from upper socio-economic class in this study. Seventy-two patients (55.38%) had suicidal attempt. Analyzed data presented that there is no association between age groups, gender and duration of disease with suicidal attempts, while there was significant association between socio economic class status and suicidal attempts. Conclusion: The suicidal attempts are highly prevalent in patients with major depressive disorders as they have batter understanding skills. Hence patients with major depressive disorders must be followed up regularly and they must have their psychotherapy to minimize the risks of suicidal attempts.